2012
DOI: 10.4103/1596-3519.96880
|View full text |Cite
|
Sign up to set email alerts
|

Biology of breast cancer in Nigerian women: A pilot study

Abstract: Our findings indicate that breast cancers in Nigerian women have a highly aggressive phenotype (high grade, hormone receptor negative), which is similar to other studies from Africa and other developing nations, as well as from African American women, but is significantly different from Caucasian women in the developed world. The presence of high numbers of TAMs in these tumors raises the possibility of targeting the immune microenvironment for therapeutic interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
23
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 29 publications
4
23
0
Order By: Relevance
“…Its incidence is rising among African women and their mortality rate is significantly higher compared to women in developed countries [1, 2]. Despite the fact that breast cancers in African women present at a younger age and at later stage [3, 4], research has demonstrated that both in their home countries and also in many Western countries, the participation of African women in breast cancer screening measures is poor [57]. …”
Section: Introductionmentioning
confidence: 99%
“…Its incidence is rising among African women and their mortality rate is significantly higher compared to women in developed countries [1, 2]. Despite the fact that breast cancers in African women present at a younger age and at later stage [3, 4], research has demonstrated that both in their home countries and also in many Western countries, the participation of African women in breast cancer screening measures is poor [57]. …”
Section: Introductionmentioning
confidence: 99%
“…1,2,3,4,5 Limited number of qualified manpower especially oncology specialists as well as lack of finances are some of the challenges identified. Various cost-effective strategies have been proposed to tackle these issues but due to the continued and glaring absence of a National cancer policy in the country; none is yet to be implemented.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies in African settings have shown high frequencies of aggressive tumour types with poorly differentiated tumours that are often hormone receptor (HR) negative. However, HR status assessment is not routinely done in many countries including Malawi [4][5][6] . This is partly due to an extreme scarcity of diagnostic pathology services in Africa .…”
mentioning
confidence: 99%